IMPLEMENTASI KEBIJAKAN KUNJUNGAN KELUARGA WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KELAS IIA BULUKUMBA - Rahmad, Rahmad; Mappamiring, Mappamiring; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of this research is to determine the implementation of the family visit policy for inmates at the Class IIA Bulukumba correctional institution using the Standards and Targets aspect approach, Communication between Institutions, External Conditions and Implementing Attitudes. This research uses qualitative research methods, namely answering a problem in detail. Data collection techniques use observation, interviews and documentation methods. The research results show (a) standards and targets, that there are SOPs and visit conditions that are known to implementers and visitors. (b) Communication between institutions and external conditions, Director General of Corrections, Ministry of Law and Human Rights relating to security coordination, implementation supervision and direction, TNI and POLRI communication, skills training for correctional officers and assistance. (c) the attitude of implementers (officers) is currently not optimal due to limited numbers and equipment, and some officers are not consistent or firm in implementing policies.